Expression and clinical significance of FGL1 and YAP1 in colorectal cancer - LIU Yuanming*，CUI Guangjie，CHEN Jiaqi，LU Yang，GAO Chao (Zhongguo linchuang yanjiu)
Objective To investigate the expression characteristics and the reationship with clinical prognostic of fibrinogen-like protein 1（FGL1）and Yes-associated protein 1（YAP1）in colorectal cancer. Methods Tissue microarray technique was used to detect FGL1 and YAP1 expression in 101 colorectal cancer tissues and 79 adjacent tissues from June 2007 to April 2008. Spearman test was employed to assess the correlation between FGL1 and YAP1 expressions. The relationship between FGL1/YAP1 expression and clinicopathological parameters was analyzed. Survival analysis was performed using Kaplan-Meier method ，and Cox proportional hazards model was used to identify risk factors influencing prognosis.Results The high expression rate of FGL1 in cancer tissues was 58.42%（59/101）， significantly higher than 30.38%（24/79）in adjacent tissues(χ2=14.022，P<0.01）. YAP1 high expression rate was 58.42%（59/101）in cancer tissues，significantly higher than 34.18%（27/79）in adjacent tissues(χ2= 10.438，P< 0.01）. FGL1 and YAP1 expressions showed positive correlation（r2=0.226，P<0.05），and their high expressions were significantly associated with lymph node metastasis and advanced TNM stage（P<0.05）. The overall survival of FGL1/ YAP1 high-expression group was significantly lower than that of the low-expression group respectively（P<0.05）. Multivariate Cox analysis revealed TNM stage（ HR=2.664，P=0.001），FGL1（ HR=2.208，P=0.016），and YAP1（ HR=1.980，P=0.030）as independent factors affecting the prognosis of colorectal cancer patients. Conclusion FGL1 and YAP1 are highly expressed in colorectal cancer tissues and associated with poor prognosis of patient ，serving as an important reference for predicting cancer progression and evaluating prognosis.